(untitled) (Research, Society and Development, 2021)
It is estimated that food allergies affect a portion of the population and have shown an increasing prevalence in recent years. Thus, the work aimed to develop a gluten-free and egg-free bisnaguinha-type bread, made with yams and a mix of flours, as a proposal for school feeding for children with food allergies. All the ingredients used for the development of this work (yam, brown rice flour, almond flour, sweet powder, potato starch, golden flaxseed flour, sugar, coconut oil, gluten-free dry biological yeast, xanthan gum, apple cider vinegar, salt and water) were acquired in the retail trade at random in the city of Barra do Piraí – RJ. The preparations were developed on a domestic scale. A mix of gluten-free flours was prepared to ensure the best result from the bisnaguinha. The preparation of nutrition labeling was based on current legislation. Through visual observation, it was possible to analyze the overall appearance of the bisnaguinhas, where they presented a soft and golden texture, typical for this type of product. It appears that a portion of 50g of bisnaguinha had 16g of carbohydrates, 3g of protein, 3g of dietary fiber, 94 mg of sodium and an energy value of 126 kcal. Regarding economic viability, it is observed that 17 bisnaguinhas cost R9.18. Concluded that the prospect for the development of gluten-free and egg-free bisnaguinhas, made with yam and a mix of flours, is promising and reached the objectives proposed in this work. For future work it is suggested to carry out microbiological and sensory analysis.